Living Hadist dan Qur’an dalam membentuk Religiusitas Anak Sejak Dini Dalam Bingkai Moderasi Beragama Di Purworejo - Nurjanah Nurjanah; Aniqoh Aniqoh; Rifqi Muntaqo (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Religious moderation is one of the most popular religious discussions today. Various religious groups interpret their religious doctrines very differently, sometimes with extreme, moderate or mediocre views. Some groups who interpret it in an extreme way lead to acts of violence and intolerance. To anticipate the occurrence of such misunderstandings and misunderstandings, it is important for us to instill good knowledge and not to interpret religious doctrines in an extreme way. One of our efforts is to provide assistance to the community's religious studies from an early age, through this activity the community can gradually change their perspective on religious doctrines that seem firm in their implementation. The community's contribution gave a positive response to the activities of living hadith and the Koran in shaping community religiosity in a sustainable manner.